Alu-deletion in Bangladeshi Women: Scopes of Clinical Utility for the Detection of Early Breast Cancer as a Biomarker - Sultana, Gazi Nurun Nahar; Sharmin, Dilruba; Jahan, Iffat; Asaduzzaman, Mohammad; Begum, Rokeya; Paul, Anindita; Rahman, M Mizanur (Asian Pacific Journal of Cancer Biology, 2022)
Objective: Alteration of Alu elements of human DNA may result cancer. This study was aimed to find status of Alu-deletion among breast cancer patients. Methods: To identify Alu-deletion, tissue samples from the operated specimen and blood of the breast cancer patients were collected. For comparison, blood was collected from healthy controls. After extraction, DNA was amplified by PCR with Alu specific primer and gel electrophoresis was done. Alu specific banding patterns of DNA of the samples were examined and compared. Result: Among the 64 patients and equal number (64) of healthy women examined, multiple Alu polymorphic loci have been identified. One of them characterized as deletion at the 2000bp region, found in 83% cancerous blood samples and only 3% in the healthy controls (p < 0.0001), OR 149. Another band was identified as less intensified at the 1700bp, present in 74% cancerous blood samples (p < 0.0001). We also found differential DNA banding pattern between breast cancer (7-9) and control blood samples (9-15) which is highly significant (p < 0.0001). Whereas no such banding pattern was observed in cancer tissues and normal breast tissues collected during surgery. Conclusion: This study confirms significant presence of Alu-deletion in women with breast cancer in comparison without cancer. Alu-deletion can be presumed as a useful blood-based biomarker for the detection of early breast cancer.